Pre and Postmenopausal Changes of Bone Mineral Density: A Comparative Study done by Dual Energy X-Ray Absorptiometry (Bangladesh Journal of Medicine, 2013)
Background: Accelerated decline of bone mass occurs in women after the menopause, and might lead to excessive bone resorption and eventually to osteoporosis. To find out the changes of bone mineral density (BMD) before and after menopause, the shown was undertaken. Materials and Methods: This comparative study was conducted in the Department of Medicine, Sylhet M A G Osmani Medical College Hospital, Sylhet during July 2008 to June 2009. Forty postmenopausal women; monthly income and BMI matched 40 premenopausal women were selected according to inclusion and exclusion criteria. BMD of lumber vertebrae and femoral neck was determined using Dual energy x-ray absorptiometry (DXA) method (Norland XR 46, Pencil beam). Results: The parity of the postmenopausal women was significantly higher than that of premenopausal women (6.9 ± 2.6 vs 3.1± 1.5; p